Anticancer Properties of Traditional Chinese Medicine - Yan, Zhaokun; Lai, Zijun; Lin, Jiumao (Combinatorial Chemistry & High Throughput Screening, 2017)
Background: Cancer is a systemic disease. Cancer occurrence is associated with several factors, including cell proliferation, apoptosis, metastasis, tumor microenvironment and immune system. Traditional Chinese medicine (TCM) has been widely used for thousands of years in China for its anti-cancer therapeutic effect. The advantage of using TCM is related to its action on multiple signaling pathways and molecular targets related to cancer, whilst causing few adverse effects. Objective: The review focuses on the most recent studies on TCM through examples that demonstrate the anticancer effects and the mechanisms. Conclusion: The review shows a large number of works which demonstrated that TCM is useful in the treatment of various types of cancers through different mechanisms of action. The results indicate that TCM exerts its anticancer effects through apoptosis induction, proliferation inhibition, metastasis suppression, multidrug resistance reversal and immune function regulation. Moreover, TCM can improve patients' quality of life. The advantage of TCM suggests that TCM may represent a promising therapeutic approach for patients with diverse cancers.
Keywords: mechanism